2022
DOI: 10.1128/spectrum.01893-22
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Methanococcus voltae Grown in the Presence of Mineral and Nonmineral Sources of Iron and Sulfur

Abstract: Clusters of iron and sulfur are key components of the active sites of enzymes that facilitate microbial conversion of light or electrical energy into chemical bonds. The proteins responsible for transporting iron and sulfur into cells and assembling these elements into metal clusters are not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This study provides the groundwork for the full elucidation of the mechanism utilized by Methanosarcina barkeri to access nutrients (Fe, S) from inert, Earth-abundant iron-sulfur minerals including FeS 2 . This work builds upon many previous analyses, including an analogous investigation on the proteome of Methanococcus voltae ( 27 ). Steward et al showed a greater degree of overall abundance changes (40% of identified proteins) in the comparison of M. voltae grown on FeS 2 compared with Fe(II)/HS − .…”
Section: Discussionmentioning
confidence: 90%
“…This study provides the groundwork for the full elucidation of the mechanism utilized by Methanosarcina barkeri to access nutrients (Fe, S) from inert, Earth-abundant iron-sulfur minerals including FeS 2 . This work builds upon many previous analyses, including an analogous investigation on the proteome of Methanococcus voltae ( 27 ). Steward et al showed a greater degree of overall abundance changes (40% of identified proteins) in the comparison of M. voltae grown on FeS 2 compared with Fe(II)/HS − .…”
Section: Discussionmentioning
confidence: 90%
“…Deletion of Ehb hydrogenase changed the abundance of 10% of all detected proteins in comparison to the wild type ( 27 ). In M. voltae , iron and sulfur depletion affected the abundance of 40% of the proteome ( 33 ).…”
Section: Discussionmentioning
confidence: 99%